Anti-angiogenic effects of cationic zinc (II) phthalocyanine derivatives through photodynamic therapy - Seyma Isik; Mukaddes Ozcesmeci; Ayfer Kalkan Burat; Esin Hamuryudan; Ozge Can; Muge Serhatli (Scientific Reports)
Abstract In this study, the in vitro photodynamic therapy (PDT) activity of two zinc phthalocyanines (ZnPc1 and ZnPc2) was systematically examined in human umbilical vein endothelial cells, focusing on PDT-induced cytotoxicity, reactive oxygen species (ROS) generation, and inhibition of angiogenic processes. Both the ZnPcs demonstrated minimal cytotoxicity in the absence of light, confirming their safety as photosensitizers. ZnPc-PDT led to significant cell death via apoptosis. ZnPc1 exhibited enhanced ROS generation, particularly at elevated concentrations. Furthermore, ZnPc1-mediated PDT showed more pronounced inhibition of endothelial cell migration, invasion, and capillary-like tube formation than ZnPc2. Wound-healing assays revealed a substantial delay in human umbilical vein endothelial cell (HUVEC) migration following ZnPc1-PDT, which also displayed a more significant inhibition of VEGF-induced directional migration and invasion. Endothelial tube formation was more effectively disrupted by ZnPc1-PDT, even at lower concentrations, compared to ZnPc2. Collectively, these findings highlight the superior cytotoxic and anti-angiogenic properties of ZnPc1 compared with ZnPc2, highlighting its potential as a highly effective photosensitizer for photodynamic therapy. The ability of ZnPc1 to simultaneously target tumor cells and disrupt angiogenesis establishes it as a potent candidate for integrated cancer therapies that combine both antitumor and antiangiogenic strategies, offering a more effective approach to combat cancer progression.